Hydrocarbon generation potential and thermal maturity of the outcropped Palaeozoic formations from Khabour Valley, Kurdistan Region, Northern Iraq - Mohammed, Aram Rafiq (Sulaimani Journal for Pure and Applied Sciences, 2023)
In this study, 12 outcropped rock samples from the Khabour, Kaista, Ora, and Harur formations (Paleozoic) in the Khabour Valley were studied. The location is in northern Iraq, in the Imbricated Thrust Zone, northeast of Duhok City. Rock-Eval Pyrolysis was utilized to assess the thermal maturity, organic matter composition, hydrocarbon potential, and organic richness of the Khabour, Kaista, Ora, and Harur formations situated within the Khabour Valley. The content of Total Organic Carbon ranges from 0.19 to 0.37 wt.%, with an average of 0.29 wt.% for the Khabour formation, 2.07 to 3.09 wt.% for the Kaista formation, 0.58 wt.% for the Ora formation, and 0.31 to 1.55 wt.% for the Harur formation. The source rock was rated poor based on the TOC wt.% content. According to the results, the Khabour Valley formations have low amounts of S2 (average 0.12 mg HC/g Rock, range 0.01-0.29 mg HC/g Rock) and Hydrogen Index (HI) (average 15.2 mg HC/g TOC, range 2-41 mg HC/g TOC). Drawing insights from the analysis of Rock-Eval data, the formations exhibit kerogen types classified as type IV kerogen. According to the cross plot of S2 versus TOC%, all the samples show a poor potentiality to create hydrocarbons. The graph of HI vs Tmax demonstrates that Tmax ranges from immature to postmature.
Keywords: Khabour; Kaista; Ora; Harur; Palaeozoic; Hydrocarbon potentiality; Thermal Maturity; Kurdistan; Iraq